Upliftment of arid zone economy through horticultural and protected cultivation - Meghwal, P. R.; Singh, Akath; Kumar, Pradeep; Khapte, P. S.; Saxena, Anurag (Indian Farming, 2018)
Climatic vagaries of arid zones make cultivation of annual crops risky and unsustainable. Horticultural sector proved beyond doubt its potentiality for gainful economy in such fragile ecosystems. Immense opportunity existed in arid zone for quality production of some of the most water economizing horticultural crops. In recent years arid and semi-arid regions witnessed a greater shift from traditional to commercial horticulture with constant government support and technical input of research and development institutions. Technologies developed on ber, pomegranate, date palm and other arid fruits by Central Arid Zone Research Institute, Jodhpur, Rajasthan showed significant impact on development of dry regions at national level. However, after near plateau for some time, horticultural scene in arid region was brightened up with introduction of newer options viz. commercial tissue culture techniques in date palm and pomegranate, protected cultivation of high value crops and new varieties and technologies in region’s adapted species. However, expanding the scale of horticultural production is often hindered by lack of market access, technological awareness and abiotic stresses.